2018
DOI: 10.1186/s12891-018-2140-5
|View full text |Cite
|
Sign up to set email alerts
|

Single cut distal femoral osteotomy for correction of femoral torsion and valgus malformity in patellofemoral malalignment - proof of application of new trigonometrical calculations and 3D-printed cutting guides

Abstract: BackgroundThe purpose of this study was to perform a derotational osteotomy at the distal femur, as is done in cases of patellofemoral instability, and demonstrate the predictability of three-dimensional (3D) changes on axes in a cadaveric model by the use of a new mathematical approach.MethodsTen human cadaveric femurs, with increased antetorsion, underwent a visually observed derotational osteotomy at the distal femur by 20°, as is commonly done in clinics. For surgery, a single cut osteotomy with a defined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…In a cadaveric model, Kaiser et al demonstrated that femoral derotational osteotomy has a significant impact on patellar tilt and axial plane engagement with a modest change in the TT–TG distance [ 113 ]. Several studies have evaluated the use of 3D-printed cutting guides both in cadaveric specimens and in vivo with promising results which may serve to provide precise and reproducible osteotomy correction in multiple planes with less radiation exposure to patients [ 114 , 115 , 116 , 117 , 118 , 119 ]. Our preferred technique is a midshaft femoral derotational osteotomy over an antegrade intramedullary nail.…”
Section: Treatmentmentioning
confidence: 99%
“…In a cadaveric model, Kaiser et al demonstrated that femoral derotational osteotomy has a significant impact on patellar tilt and axial plane engagement with a modest change in the TT–TG distance [ 113 ]. Several studies have evaluated the use of 3D-printed cutting guides both in cadaveric specimens and in vivo with promising results which may serve to provide precise and reproducible osteotomy correction in multiple planes with less radiation exposure to patients [ 114 , 115 , 116 , 117 , 118 , 119 ]. Our preferred technique is a midshaft femoral derotational osteotomy over an antegrade intramedullary nail.…”
Section: Treatmentmentioning
confidence: 99%
“…In order to improve the precision of bone axis alterations, these procedures have recently been used to reach the desired outcome [ 20 ]. Therefore, easy-to-handle tools, such as customized cutting guides, could help surgeons to increase the precision of a surgical procedure [ 21 ]. Cutting guides are easy to place and generally ensure unequivocal positioning [ 22 ]; custom cutting guides have recently been introduced as a more accurate and efficient methodology for orthopedic surgery [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16] Single-cut osteotomies are also described in the human literature, mainly for treating fracture malunion. [17][18][19][20][21][22][23] A single-cut osteotomy is performed in the plane of maximal deformity, and correction is subsequently achieved by rotation and potentially translation of the opposing bone surfaces. The single-cut osteotomy's main advantage is the increased bone contact, which facilitates a stable fixation and accelerates bone healing.…”
Section: Introductionmentioning
confidence: 99%